Strategic Implementation of Maternal, Neonatal, Child Health and Nutrition Health Programs in Ilocos Sur, Philippines - Bermio, Joussie Bajet (JPAIR Multidisciplinary Research, 2015)
The Department of Health is committed to achieve the Millennium Development Goals of reducing child mortality and improving maternal health by 2015.The study aimed to determine the relationship between the extent of implementation of the maternal, neonatal, child health, nutrition strategy, and the socio-demographic, work-related and health facility-related factors. The study employed the descriptive-correlational method. The respondents were all the 244 municipal health office personnel of Ilocos Sur, Philippines. The DOH guideline was partially adapted specifically on natal and post- natal part of the questionnaire. The extent of implementation of the MNCHN Strategy is "Very High"; the implementer-respondents’civil status yielded positive significant relationship while the implementer-respondents’ educational attainment yielded an inverse significant relationship with the extent of implementation of the MNCHN Strategy. Moreover, the number of health personnel, consultation, and delivery room equipment are significantly related to the implementation of the MNCHN Strategy. The local government unit of Ilocos Sur, Philippines is on the process of finalizing the ordinance in support to the MNCHN Strategy and the Department of Health is also working on Health Facility Enhancement Program (HEP) so that the Municipal Health Offices could upgrade their equipment in providing higher quality of health services to the community.